The relationship between predisposing, enabling, and reinforcing factors regarding topical fluoride application and the risk of dental caries among firstgrade elementary school students in the Tambakrejo Health Center Area - Dini Setyowati; Hadfi Dhaky Chairuly; Benedicta Sellyvia; Nur Aini Nova Airlangga; Widya Ayu Satya Pratiwi; Mokhammad Fauzi; Amanda Ayu Aprilia; Jasmine Dharmarani Saputra; Sella Pujaya Wahyu Aifma; Fanya Suryanti; Tengku Natasha Eleena binti Tengku Ahmad Noor (Faculty of Dental Medicine Universitas Airlangga, 2026)
Background: Dental caries is a common oral health issue among school-aged children, often influenced by parental knowledge, socioeconomic conditions, and access to preventive care. Based on Lawrence W. Green’s theory, health behavior is determined by predisposing, enabling, and reinforcing factors. Purpose: This study aimed to analyze the factors influencing the implementation of topical fluoride application and their relationship with dental caries risk among first-grade students in the Tambakrejo Public Health Center area. Methods: This cross-sectional study was conducted from July 21–22, 2025, involving 67 parents of first-grade students from Darussalam Islamic Elementary School, Kapasan III Public Elementary School, and Muhammadiyah 17 Elementary School, Surabaya. Data were collected using questionnaires on predisposing, enabling, and reinforcing factors. Caries risk was assessed using a Cariogram interview. Correlations were analyzed with Spearman’s Rho test with SPSS. Results: Parental knowledge (r = -0.719; p = 0.000), access to information (r = -0.622; p = 0.000), economic status (r = -0.331; p = 0.006), and health program support (r = -0.383; p = 0.001) were significantly and negatively correlated with caries risk. Reinforcing factors such as social (r = -0.723; p = 0.000), informational (r = -0.711; p = 0.000), and tangible support (r = -0.838; p = 0.000) also showed strong negative correlations, while emotional support (r = 0.026; p = 0.834) was not significant. Conclusion: Predisposing, enabling, and reinforcing factors significantly influence children’s dental caries risk. Enhanced parental knowledge and support effectively reduce caries risk.